2016
DOI: 10.1007/s13280-016-0808-3
|View full text |Cite
|
Sign up to set email alerts
|

Can private management compensate the ineffective marine reserves in China?

Abstract: Marine reserves (MRs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…The reduced feeding rate of grazers on the reef at in the general use zone was a speculated result of anthropogenic interference. Huang et al (2017) found sh abundance and diversity were signi cantly reduced in the presence of many tourists without management. The reef ats of general use zone in this study are subject to snorkelling, swimming and shing.…”
Section: Discussionmentioning
confidence: 90%
“…The reduced feeding rate of grazers on the reef at in the general use zone was a speculated result of anthropogenic interference. Huang et al (2017) found sh abundance and diversity were signi cantly reduced in the presence of many tourists without management. The reef ats of general use zone in this study are subject to snorkelling, swimming and shing.…”
Section: Discussionmentioning
confidence: 90%
“…The most effective method to promote sustainability is for the government to give authority for making management decisions only to the stakeholders who immediately rely on the resources (Anonymous 2000;Huang et al 2016). The Constitution of the Republic of Palau begins by stating that Often-defined Overfishing UNSTABLE STABLE Fig.…”
Section: Adjustive Management At the Village Levelmentioning
confidence: 99%
“…Japanese and westerners should have no trouble being served open-ocean fishes in Palau, but the Chinese and Taiwanese appear to have a propensity for choosing reef fishes. Much of the live-reef-fish trade is to Hong Kong, China and Taiwan where restaurants still serve coral-reef fishes (Huang et al 2016). This may be a problem for Palau where 61% of the visitors in 2015 were from China and Taiwan.…”
Section: Export From Coral Reefs Is Not Naturalmentioning
confidence: 99%
“…Additionally, the prevalence of coral disease has also been linked to anthropogenic disturbances such as the waste and pollution associated with intense tourism operations (Lamb and Willis 2011;Lamb et al 2014). Illegal collection of corals by tourists has also been observed near tourism centers that encourage such acts by selling shells and corals for decoration purposes (Huang et al 2017). Evaluating the influence of tourist activities on coral reef environments should therefore be critical for effective tourism management and sustainable use of coral reefs.…”
Section: Introductionmentioning
confidence: 99%